2021
DOI: 10.1186/s40001-021-00548-0
|View full text |Cite
|
Sign up to set email alerts
|

First case of low-dose umbilical cord blood therapy for pediatric acute respiratory distress syndrome induced by Pneumocystis carinii pneumonia

Abstract: Objective This study aimed to present the case of a boy with acute distress syndrome (ARDS) treated with low-dose umbilical cord blood (UCB) therapy and explore the underlying possible mechanism. Methods A 7-year-old boy with severe Pneumocystis carinii pneumonia and severe ARDS was treated with allogeneic UCB as salvage therapy. Results The patient did not improve after being treated with lung protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Consequently, there is a long way in front before it is widely used in clinical antiviral therapy. In the case of umbilical cord blood, rich in hematopoietic stem cells and various types of immune active cells, it can be induced to differentiate into functional mature cells, leading to complete immune initiation and regulation ( 142 , 143 ). Shuang Liu et al reported that they used low-dose umbilical cord blood to successfully treat acute respiratory distress syndrome caused by Pneumocystis carinii pneumonia ( 143 ).…”
Section: Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, there is a long way in front before it is widely used in clinical antiviral therapy. In the case of umbilical cord blood, rich in hematopoietic stem cells and various types of immune active cells, it can be induced to differentiate into functional mature cells, leading to complete immune initiation and regulation ( 142 , 143 ). Shuang Liu et al reported that they used low-dose umbilical cord blood to successfully treat acute respiratory distress syndrome caused by Pneumocystis carinii pneumonia ( 143 ).…”
Section: Therapymentioning
confidence: 99%
“…In the case of umbilical cord blood, rich in hematopoietic stem cells and various types of immune active cells, it can be induced to differentiate into functional mature cells, leading to complete immune initiation and regulation ( 142 , 143 ). Shuang Liu et al reported that they used low-dose umbilical cord blood to successfully treat acute respiratory distress syndrome caused by Pneumocystis carinii pneumonia ( 143 ). What is more, traditional Chinese medicine is also one of the potential treatments for severe adenovirus pneumonia.…”
Section: Therapymentioning
confidence: 99%
“…Considering the marginal hemodynamic status and the severe cardiac dysfunction, together with 30 min cardiopulmonary resuscitation after the cardiac arrest, and large dose of inotropic agents, we chose to perform extracorporeal membrane oxygenation (ECMO) to support the cardiopulmonary circulation. ECMO is widely utilized in Covid patient with severe pulmonary dysfunction, it provides a new approach for clinical practice [ 1 , 2 ]. Meanwhile, after continuous chest compressions and multiple electrical de-fibrillation, on many occasions, the patient can recovery to normal sinus arrhythmia, but few minutes later, ventricular fibrillation repeated occurred alternately.…”
Section: Case Presentationmentioning
confidence: 99%
“…AFE is an obstetrical catastrophic syndrome, which occurs when amniotic fluid has entered maternal circulation causing respiratory failure, coagulation dysfunction and other pathological changes of obstetrical specific severe syndromes [ 1 ]. Despite rare, AFE remains one of the leading causes of direct maternal mortality (up to 86%) in high-income countries [ 2 ]. Therefore, collecting and reporting related cases is of great significance for guiding clinical practice.…”
Section: Introductionmentioning
confidence: 99%